2020
DOI: 10.1038/s41598-020-66718-y
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bri3 BRICHOS domain is a molecular chaperone with effect against amyloid formation and non-fibrillar protein aggregation

Abstract: Molecular chaperones assist proteins in achieving a functional structure and prevent them from misfolding into aggregates, including disease-associated deposits. The BRICHOS domain from familial dementia associated protein Bri2 (or ITM2B) probably chaperones its specific proprotein region with high β-sheet propensity during biosynthesis. Recently, Bri2 BRICHOS activity was found to extend to other amyloidogenic, fibril forming peptides, in particular, Alzheimer's disease associated amyloid-β peptide, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…However, ImmuMethy revealed that cg15127563, which is found within the ITM2C gene (integral membrane protein 2C, also known as BRI3), is a novel differential methylation site with elevated methylation levels in PD patients ( Figure 5 ). In a recent study, recombinant BRI3 protein was found to function as a molecular chaperone to inhibit amyloid formation and nonfibrillar protein aggregation ( 22 ). However, whether this CpG site is involved in the development of neurodegenerative diseases awaits further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…However, ImmuMethy revealed that cg15127563, which is found within the ITM2C gene (integral membrane protein 2C, also known as BRI3), is a novel differential methylation site with elevated methylation levels in PD patients ( Figure 5 ). In a recent study, recombinant BRI3 protein was found to function as a molecular chaperone to inhibit amyloid formation and nonfibrillar protein aggregation ( 22 ). However, whether this CpG site is involved in the development of neurodegenerative diseases awaits further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to Bri2, the overall levels of Bri3 are shown to be decreased in AD, although the deposition with the amyloid plaques is similar for both Bri2 and Bri3 [202]. BRICHOS from both Bri2 and Bri3 interact with Aβ in neurons and inhibit Aβ fibrillization in vitro, but Bri3 shows less efficiency compared to Bri2 [202,203], suggesting a different role for Bri2 and Bri3 BRICHOS in Aβ pathology.…”
Section: Brichosmentioning
confidence: 90%
“…Among the BRICHOS proteins, the Bri2 and Bri3 of the BRI family play a significant role in the prevention of neurodegenerative diseases [47,193,202,203]. These proteins are highly expressed in the brain.…”
Section: Brichosmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, for the BRICHOS domains studied so far, the ability to suppress amorphous protein aggregation, the canonical molecular chaperone function, is not coupled to the ability to prevent amyloid fibril formation or toxicity. ProSP-C BRICHOS essentially lacks activity against amorphous protein aggregation, while Bri2 and Bri3 BRICHOS inhibit both fibrillar and non-fibrillar aggregation (32,34). We could recently explain the basis for this discrepancy by showing that the canonical chaperone activity to suppress amorphous protein aggregation is determined by specific loop segments in BRICHOS, while the activity against amyloid formation is independent of these segments (Chen et al, submitted for publication).…”
Section: Introductionmentioning
confidence: 99%